EFFICIENCY OF PURE LACCASE AND LIGNIN PEROXIDASE FROM PHANEROCHAETE CHRYSOSPORIUM BW808 (MTCC 787) IMMOBILIZED ON SOLID MATRIX IN DEGRADATION OF PHENOLICS FROM SEWAGE WASTE WATER - BEN MANUEL CHORAGUDI; MOWNICA VEMURI; RAJYALAKSHMI AMANCHERLA; J.A.PRASAD (International Journal of Pharma and Bio Sciences, 2016)
Active laccase and LiP fractions purified from Phanerochaete chrysosporium broth cultures designed for degradation of phenols in sewage samples were immobilized by entrapping in Sol-Gel matrix of trimethoxysilane (TMOS) and propyltetramethoxysilane (PTMS). A maximum of 90.7% and 92.3% of immobilization efficiencies were achieved with a 2 mg/mL pure laccase and pure LiP each. Immobilized laccase and LiP retained 80% and 84% of their activities at pH 4.5 and 5.5 respectively compared to free enzymes. The capacity of the enzyme laccase to withstand the effect of inhibitors (cystein, EDTA, and Ag+) was also enhanced by up to 80% by immobilization. Immobilized Laccase was active in the reaction mixture for three hours, but degraded only 45% of the phenol in one hour whereas immobilized LiP which remained active for one and half hour degraded 95% of phenol in the stipulated one hour time. When immobilized laccase was treated with divalent metal ions Ca++ and Cu++ it worked faster equal to immobilized LiP and degraded 96% phenol in one hour and remained active for 3 hours.